(untitled) (International Journal of Applied Research in Management and Economics, 2025)
University research projects usually aim to create innovations. All research and innovations inherit risks from uncertainties in the requirements or procedures. Risk management, therefore, has an important impact on the management of these projects to achieve objectives and ensure that risks are handled correctly. For this reason, this paper develops a risk management concept based on a single case study for university research projects. For this purpose, a 3D simulation of an innovative combustion process for a car engine is examined. The simulation focuses on meeting the challenges based on higher efficiency, lower emissions, and the use of alternative fuels. To investigate this at the management level, an adapted risk management procedure for the detailed combustion model is integrated into the project plan. This aims to determine if the developed model and the simulation can be used for forecasts. The project plan includes base costs (personnel resources, computer resources), uncertainties (physical model accuracy), and risks (new developments, incompatibility of the models). The model is validated using a Monte Carlo simulation, aiming to improve the handling of risks and the accuracy of the simulation. The relation between the simulation results compared to the development and computing times is examined. This procedure intends to optimise the decision-making process for models and simulations to meet the time and budget constraints, to improve the achievement of objectives, and the quality of the research results. In addition, the classification and resilience of the simulation results should be obtained and ensured.